LRST: searching tree anti-collision algorithm with low-redundancy - Qiong HUANG; Jiang-tao LING; Min ZHANG; Xiao-long YANG (Tongxin xuebao)
During the RFID tag identification process, the tree-based anti-collision algorithms usually incur large amount of redundant data due to an excess of long query commands,which increases the communication overhead. To resolve this problem, a searching tree anti-collision algorithm with low-redundancy on the basis of regressive-style dynamic searching tree algorithm was proposed. In order to reduce the number of queries, a novel query mode was developed, i.e., single query with duo responses. Depending on the most significant collided bit, the collided tags respond in the first or second slot separately. In order to reduce the length of query command, the prefix matching circuit in tag was replaced with a counter, which eliminated the prefix as the parameter of query command. The predictive identification and block-ing technique were also introduced to avoid unnecessary queries. Theoretical analysis and simulation results show that the communication overhead is greatly reduced.